The AI Alchemist. - Jing, Ji (Beijing Review, 2026)
The article focuses on Lingguang AI, a "zero-code" mini-program builder from Ant Group that enables users to create customized applications without traditional programming by using natural language prompts. Since its launch five months ago, Lingguang has facilitated the creation of 30 million apps, fostering a DIY culture where users develop tools for personal use and entrepreneurship, supported by a substantial incentive program. However, challenges remain regarding the longevity and quality of these apps, as many are single-use and face distribution limitations outside the Lingguang platform. Industry observers and users highlight concerns about data reliability, app discoverability, and the potential for quantity-driven content over sustained value, posing questions about the platform’s long-term ecosystem vitality.